Numerical Investigation on the Dynamic Responses and Failure Criterion of RC Beam Under Impact - Guo, Jinlong; Jiang, Guoping; Wu, Zhengyu; He, An; Cai, Jian (Frontiers in Materials, 2022)
During the period of service, the infrastructure would be subject to various forms of impact. To investigate the impact responses of reinforced concrete (RC) beam, a numerical model of RC beam under impact was developed by the finite element package LS-DYNA in this study. The numerical model was verified by the drop hammer test on the RC beam. Using the numerical model, the midspan displacement of RC beams is analyzed under the interaction of impact mass and impact velocity. The results show that the response surface of midspan displacement can be fitted as a binary power function of impact mass and impact velocity. The midspan displacement under various impact conditions with equal impulse or equal impact energy is different. Within the scope of low-speed impact, the midspan displacement decreases with an increase in the impact mass under the equal impulse; while it increases with an increase in the impact mass under the equal impact energy. In addition, the impact failure of the RC beam is judged by the deformation criterion. The threshold value of ductility coefficient is advised as 15 in the impact-resistant design for RC beam in civil engineering structure within the scope of low-speed impact.